Tang Wang Ming Mu Granule Attenuates Diabetic Retinopathy in Type 2 Diabetes Rats - Chen, Mingxia; Lv, Haibo; Gan, Jiakuan; Ren, Junguo; Liu, Jianxun (Frontiers in Physiology, 2017)
Aims This study aimed to determine the influence of Tang Wang Ming Mu granule (TWMM) on the diabetic retinopathy of diabetic rats. Methods Male Wistar rats were divided into seven groups: normal control, diabetes model(DM), diabetes with TWMM (3.6 g/kg, 7.2 g/kg, 14.4 g/kg) treatment, the positive control treatment groups of Qi Ming granules and Calcium dobesilate capsules. All rats were treated for 8 weeks. The levels of body weight, fasting blood glucose (FBG) and glycosylated hemoglobin (HbA1c) in blood were measured to evaluate the antihyperglycemic activity of TWMM. Furthermore, malondialdehyde (MDA), intracellular adhesion molecule-1 (ICAM-1) and vascular endothelial growth factor (VEGF) in serum were measured to study effects of TWMM on oxidative stress and inflammatory in DM2 rats. VEGF, JAK/STAT signaling pathway and SOCS3 in retina was detected by immunohistochemistry. Results TWMM and the positive control drugs Qi Ming and Calcium dobesilate showed a remarkable suppression of retinal neovascularization and amelioration of retinal internal limiting membrane morphology. Moreover, TWMM significantly decreased HbA1c, MDA, ICAM-1and VEGF levels in serum of diabetic rats. However, Qi Ming granules showed significantly reduced MDA and VEGF levels (P<0.01, and P<0.05, respectively), Calcium dobesilate showed significantly reduced MDA and ICAM-1levels (P<0.01, and P <0.05, respectively) in serum. All drug- treated DM2 rats showed significantly lower levels of VEGF, JAK2, P-JAK2, STAT3 and P-STAT3 in retina than DM group, while TWMM and Calcium dobesilate significantly increased SOCS3 in retina. Conclusion Our data suggest that the diabetic retina protective effect of TWMM might be related to antiinflammatory, antioxidative, upregulation of SOCS3 expression, inhibition of the JAK/STAT/VEGF signaling pathway.